Pembelajaran Mangaji dan Batamat Anak Usia Sekolah Dasar pada Tradisi Kalangan Masyarakat Banjar Kota Banjarmasin: Betamat Alquran dalam Tradisi Banjar (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This research aims to determine learning mangaji and batamat activities among the Banjar Community of South Kalimantan. The type of research used is descriptive because it will provide an overview of the problem through analysis using a scientific approach in accordance with the actual situation, namely to find out systematic, factual and accurate descriptions, descriptions of the facts, characteristics and relationships about Learning the Koran and Batamat for Elementary School Age Children in Traditions Among the Banjar Community of Banjarmasin City. The results of learning Mangaji in the Banjar Community Tradition in Banjarmasin City here are the activities of reading the Koran carried out by children, where there are various ways of Mangaji, including: 1) Reciting the Koran after evening prayers at home looked after by their parents, or at the mosque and at The prayer room already has a teacher teaching there. 2) Study the Koran in places where people understand the Koran. 3) Recite the Koran at TPQ (Quran Education Park). Batamat is a tradition of Muslim communities that has been carried out from generation to generation. The tradition of batamat Al-Quran is a celebratory activity when Banjar people finish reading 30 juz of the Koran. In the implementation process, all the equipment and things needed are prepared so that the batamat tradition runs smoothly. During the event, various cakes and typical Banjar ethnic foods were served. The Koran teacher will start by reading surah al-Fātihah, followed by the participants reading surah Aḍ-Ḍuḥa to surah an-Nass. Apart from that, every time you finish reading a surah you are required to read the tahlil and tahmid. Next, the Koran teacher will close the batamat activity by reading the Koran khataman prayer.